1980
DOI: 10.1039/c39800000601
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure (X-ray analysis) of marcfortine A, a new alkaloid from Penicillium roqueforti

Abstract: The structure of marcfortine A, a novel alkaloid isolated from Penicilliurn roqueforti, has been established by X-ray analysis; two minor alkaloids, marcfortine B and C, as well as the previously known roquefortine have also been isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…NOESY interactions between H-21, H-12a, H-10b, H-23 and H-24 placed the corresponding substituents together on the frontal face of the cyclopentanoid ring. The relative stereochemistry proposed for 1 is in agreement with the relevant features of the relative stereochemistry of marcfortine A [7]. The Cotton effect at 200ϳ250 nm arises from an n-p * transition of the diketopiperazine amide bonds, which is diagnostic for the bicyclo-[2.2.2] diazaoctane diketopiperazine core [10,11].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…NOESY interactions between H-21, H-12a, H-10b, H-23 and H-24 placed the corresponding substituents together on the frontal face of the cyclopentanoid ring. The relative stereochemistry proposed for 1 is in agreement with the relevant features of the relative stereochemistry of marcfortine A [7]. The Cotton effect at 200ϳ250 nm arises from an n-p * transition of the diketopiperazine amide bonds, which is diagnostic for the bicyclo-[2.2.2] diazaoctane diketopiperazine core [10,11].…”
Section: Resultssupporting
confidence: 75%
“…Since 6 out 12 unsaturations were accounted for, 1 was inferred to contain six rings. Further evaluation of these spectral data, along with 1 H-1 H COSY and HMBC results, revealed that 1 is closely related to the marcfortine group of fungal metabolites [7]. Interpretation of HMBC correlations (Fig.…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 94%
“…[1] A common feature of this complex compound progeny is the substitution of the indole C-3 position, a pattern present in several 3,3-spirofused and 3,4-bridged oxindoles, such as marcfortine B, [2] welwitindolinone C, [3] and gelsemine [4] core structures ( Figure 1). These motives can be realized in diverse synthetic ways, among which the direct or indirect aldol-, Mannich-, and Michael-type C-3 Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because the marcfortines and paraherquamides are unique both structurally and in their mode of action, they represent a promising new class of anthelmintics. Marcfortine A (1), a fungal metabolite of Penicillium roqueforti reported by Polonsky et al, 4 is structurally related to paraherquamide A (2) which was originally isolated from P. paraherque. 5 Paraherquamide A (2) contains a five-membered G-ring possessing a hydroxyl group and a methyl group, whereas the G-ring of marcfortine A (1) is six membered (Figure 1).…”
Section: Introductionmentioning
confidence: 99%